Antisocial behavior by young people / Michael Rutter, Henri Giller, Ann Hagell. - Rutter, Michael, 1962- (Cambridge University Press, 1998)
"Written by a child psychiatrist, a criminologist, and a social psychologist, Antisocial Behavior by Young People is a major international review of research evidence on antisocial behavior. The book covers all aspects of the field, including descriptions of different types of delinquency and time trends, the state of knowledge on the individual, social-psychological and cultural factors involved, and recent advances in prevention and intervention. The authors bring together a wide range of disciplinary perspectives in order to provide a comprehensive account of antisocial behavior in youth."--Jacket.